Assessing the relationship between health literacy intervention and hypertension self-management: A 7-year systematic review from January 2016 to December 2022 - Feyisayo Iyabo Bamidele; Cecilia Bukola Bello; Oladayo Damilola Akinwale; Mubo Stella Falana (Wolters Kluwer Medknow Publications, 2024)
Hypertension (HTN) is one of the most common chronic diseases affecting over 30% of the adult population globally, with a growing incidence rate. This review assesses the relationship between health literacy (HL) intervention and hypertension (HTN) self-management among people with HTN. The study design was a systematic review of empirical research articles using a well-defined strategy. Online journals were accessed through databases such as PubMed, CINAHL, Google Scholar, ProQuest, Global Health, WHOLIS, Embase, and EbscoHost, spanning from January 2016 to December 2022 as the scope of the study. Articles selected for inclusion were those published in English during the specified time frame and adhering to Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines and Sample, Phenomenon of Interest, Design, Evaluation, Research Type framework for systematic review, focusing on criteria related to the sample, the phenomenon of interest, study design, evaluation, and research type. Out of 180 studies initially identified in the database search, 20 studies were ultimately included in the review. The findings were reported based on these five emerging themes: Relationship between HL and HTN self-management; Effect of HL intervention on HTN self-management; Factors predicting self-care behaviors among HTN patients with low HL; Effect of HL and self-management efficacy on health-related quality of life (HRQoL); and level of self-care practices. This review highlights a relationship between HL, self-efficacy, self-care, and HRQoL, underscoring the necessity for further well-designed intervention studies focused on enhancing HL in individuals with HTN in Nigeria to enhance their quality of life.